Regulation of Nanomaterials and Nanomedicines for Clinical Application - Ahmed, Razi; Maurya, Vikash; Dwivedi, Anurag; Mishra, Manoj Kumar (Applied Drug Research, Clinical Trials and Regulatory Affairs, 2024)
Treatment of complicated fatal diseases was difficult when nanotechnology was not more popular. The incorporation of nanomedicine has increased in the last 13 years, even though regulatory guidelines regarding nanomaterials and nanomedicine weren't sufficient. Hence, it was tough to decide valid inevitability for the manufacturers, administrators, health professionals, primary care providers, and rest of the public that could ultimately have a negative impact on the financing system, research, and development of such items, affecting the approval of the public and acceptance of nano-products. This review includes coverage across the therapeutic value of nanomaterials, problems in the regulation, regulatory challenges, synthesis, physicochemical properties, and clinical application. The hurdles to using nanotechnology, particularly in the pharmaceutical development of novel medicinal products and respective regulatory issues, are critically explored, considering the characteristics offered by the nanomaterials.
Keywords: nanomedicine